The development of compensatory ability for a sexually-selected ornament in stalk-eyed flies - Vance, Jason T.; Swallow, John G. (Frontiers in Ethology, 2024)
Female preference for longer eyespan has driven exaggerated sexual dimorphism in several species of stalk-eyed flies. Longer eyespan increases a fly’s moment of inertia, and flies experience significant increase in body mass across age as they mature sexually. These costs may impact flight behavior and fitness through maneuverability and predator evasion, and appear ameliorated by co-selection for compensatory traits, as flies with longer eyespans tend to have larger thoraces and wings, allowing them to perform turns similar to flies with shorter eyespans. However, the capacity to compensate for a potentially costly ornament may not be limited to morphological traits which are fixed at the time of eclosion: as flies age, they also accumulate thorax mass and improve their flight performance. The purpose of this study was to investigate the compensatory ability of two populations of stalk-eyed flies (Teleopsis dalmanni and Diasemopsis meigenii) through comparing morphology and flight performance relative to eyespan. ‘Over-compensators’ should exhibit greater morphological and/or performance traits relative to eyespan, whereas ‘under-compensators’ should exhibit relatively less across these metrics. Flight performance was assessed using high-speed videography and variable-density gas-mixtures to determine maximal flight capacity. Young adult flies eclosed as ‘under-compensators’, with less thorax mass, wing velocity and flight capacity relative to their eyespan as compared to older flies. As flies aged and accumulated thorax mass, they became ‘over-compensators’. Thus, compensation for long eye-stalks is not a fixed trait; instead, variation in compensatory ability appears to be associated with the development of thorax muscle and flight performance across age.